Resistance training increases skeletal muscle oxidative capacity and net intramuscular triglyceride breakdown in type I and II fibres of sedentary males. Issue 6 (6th May 2014) - Shepherd, S. O.; Cocks, M.; Tipton, K. D.; Witard, O. C.; Ranasinghe, A. M.; Barker, T. A.; Wagenmakers, A. J. M.; Shaw, C. S.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Recent research from our laboratory, supported by in vitro effects of perilipins, suggested that improvements in insulin sensitivity following endurance training are mechanistically linked to increases in muscle oxidative capacity, intramuscular triglyceride utilization during moderate endurance exercise and increases in the content of the lipid droplet‐associated perilipins 2 and 5. This study aimed to investigate whether these adaptations also occur in response to resistance training. What is the main finding and its importance? Six weeks of resistance training increased all the mentioned variables. These novel data suggest that improvements in muscle oxidative capacity and lipid metabolism contribute to the increase in insulin sensitivity following resistance training. Recent in vitro and in vivo experimental observations suggest that improvements in insulin sensitivity following endurance training are mechanistically linked to increases in muscle oxidative capacity, intramuscular triglyceride (IMTG) utilization during endurance exercise and increases in the content of the lipid droplet‐associated perilipin 2 (PLIN2) and perilipin 5 (PLIN5). This study investigated the hypothesis that similar adaptations may also underlie the resistance training (RT)‐induced improvements in insulin sensitivity. Thirteen sedentary men (20 ± 1 years old; body mass index 24.8 ± 0.8 kg m−2) performed 6 weeks of whole‐body RT (three times per week), and changes in peak O2 uptake (in millilitres per minute per kilogram) and insulin sensitivity were assessed. Muscle biopsies (n = 8) were obtained before and after 60 min steady‐state cycling at ∼65% peak O2 uptake. Immunofluorescence microscopy was used to assess changes in oxidative capacity (measured as cytochrome c oxidase protein content), IMTG and PLIN2 and PLIN5 protein content. Resistance training increased peak O2 uptake (by 8 ± 3%), COX protein content (by 46 ± 13 and 61 ± 13% in type I and II fibres, respectively) and the Matsuda insulin sensitivity index (by 47 ± 6%; all P < 0.05). In type I fibres, IMTG (by 52 ± 11%; P < 0.05) and PLIN2 content (by 107 ± 19%; P < 0.05) were increased and PLIN5 content tended to increase (by 54 ± 22%; P = 0.054) post‐training. In type II fibres, PLIN2 content increased (by 57 ± 20%; P < 0.05) and IMTG (by 46 ± 17%; P = 0.1) and PLIN5 content (by 44 ± 24%; P = 0.054) tended to increase post‐training. Breakdown of IMTG during moderate‐intensity exercise was greater in both type I and type II fibres (by 43 ± 5 and 37 ± 5%, respectively; P < 0.05) post‐RT. The results confirm the hypothesis that RT enhances muscle oxidative capacity and increases IMTG breakdown and the content of PLIN2 and PLIN5 in both type I and type II fibres during endurance‐type exercise.